MODEL PENAFSIRAN MAINSTREEM DAN NON-MAINSTREEM (Tinjauan atas penafsiran Ayat dan Hadis Hisab Ru’yah) - Mushonnif, Ahmad (INOVATIF: Jurnal Penelitian Pendidikan, Agama dan Kebudayaan, 2020)
Differences related to the establishment of the beginning of the month of Hijriyah, especially in Indonesia, are related to the model of interpretation of the Qur'anic texts and the traditions related to them. Based on typology, there are three interpretive models, namely the bi al-Ma'thu> r interpretation model that gives rise to the Rukyat madhhab, bi al-Ra'y Madhhab Hisab, both are mainstream and Isyari> which give rise to non-mainstream madhhab with methods such as the use of the inner eye , dreamy with a black cloth, using certain numbers and others. Each of these interpretive models colors the pattern of Muslim thought, especially in Indonesia